Pemanfaatan Software Heat Transfer Research Inc. (HTRI) dalam Perancangan Double-Pipe Heat Exchanger - Ronald Akbar (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2023)
The design of a double-pipe heat exchanger has been carried out. This study aimed to compare the overall heat transfer coefficient from the double pipe heat exchanger design with the HTRI software output results. The overall heat transfer coefficient value in the manual calculation process is 221.53 W/m2K. The design process with HTRI software was carried out by inputting data from design cases into the software. From the running results, the overall heat transfer coefficient is 213.58 W/m2K. The results compared to produce a deviation of 3.67%. The results of this deviation are considered very good because it is far below the deviation value targeted in this study, which is .  The HTRI software is beneficial as a validation tool and a complement to the heat exchanger design process.